Efficacy of Combination Chemo-Immunotherapy as a First-Line Treatment for Advanced Non-Small-Cell Lung Cancer Patients With HER2 Alterations: A Case Series - Zhao, Shuang; Xian, Xinghong; Tian, Panwen; Li, Weimin; Wang, Ke; Li, Yalun (Frontiers in Oncology, 2021)
Objective Although the treatment of non-small-cell lung cancer (NSCLC) patients with human epidermal growth factor receptor 2 (HER2) alterations has been studied for years, the overall response rate (ORR) of these patients is still unsatisfactory, and more therapeutic strategies are needed. Little is known about the combination of chemo- and immunotherapy in HER2-altered lung cancer treatment. Materials and Methods We report five cases of advanced NSCLC with HER2 insertion mutation or amplification treated with immunotherapy combined with chemotherapy as the first-line treatment. The HER2 alteration type, duration of treatment and survival were also analyzed. Results The five advanced NSCLC patients, three with HER2 mutations and two with HER2 amplifications, received chemo-immunotherapy as the first-line treatment. The average patient age was 54.6 years. Three patients were females, and two were males. Among all the patients, only one had a smoking history. The immunotherapies used were as follows: two patients were treated with sintilimab, and three patients were treated with pembrolizumab. Only one patient had squamous carcinoma, and she was also the only patient with a complete response (CR). The progression-free survival (PFS) ranged from 2-12 months, with a median PFS of 8.0 months. Conclusions Chemo-immunotherapy may be a promising first-line treatment option for NSCLC patients with HER2 alterations. Further clinical trials are required to confirm this therapeutic option.